How school principals form their leadership identity - Saarukka, Siv (Vodenje v vzgoji in izobraževanju, 2014)
The aim of this study is to discuss how school principals form their leadership identity on personal, professional and positional levels in leadership practice. Aspects about identity are analysed through the outcomes of empirical material from interviews about creating professional school leadership. According to identity theories and empirical findings, the mutual process of awareness of contents in leadership and their influences on the principal as a person, the principalship as a profession and the formal leadership position are essential elements when forming the leadership identity. To be a school principal is a complex profession, but creating the leadership identity in relation to different aspects in principalship is one way of developing structure in understanding leadership. Findings show proof of connections between awareness about identity and success in school leadership. Struggle in the process of identity building was also recognized, and reasons causing failing leadership was identified as related to undeveloped identity. Forming school leadership identity was identified as a continuing relational process developed through communication and activities where teachers confirm the principal as a person, in the professional role, and in the leadership position.
Keywords: education; identiteta; identity; leadership; principal; profession; ravnatelji; vodenje